Boosting the electrocatalytic performance of Pt, Pd and Au embedded within mesoporous cobalt oxide for oxygen evolution reaction. (2nd August 2018) - Qu, Qing; Pan, Guo-Liang; Lin, Yan-Ting; Xu, Chang-Wei
Abstract : High efﬁcient and low-cost electrocatalysts for the oxygen evolution reaction (OER) are essential components of renewable energy technologies. However, the high onset potential and limited active sites restrict the catalytic activity of current electrocatalysts. Therefore, we are motivated by the development of cheap and efficient catalytic electrodes to promote the sluggish water-splitting systems associated with the large-scale application of clean and renewable energy technologies. Herein, a novel, simple, and efficient routine is presented by noble metal particles embedded within mesoporous metal oxide materials as high-efficiency anode catalysts for OER. Highly ordered mesoporous Co3 O4 was prepared by a nanocasting method using the silica KIT-6 as hard template, showing an enhanced electrochemical performance. Then, M - Co3 O4 (M = Pt, Pd, Au) nanomaterials were prepared by a simple but novel chemical reduction method. They show the high surface area of 112.3, 81.0 and 73.6 m 2 g −1, which can provide more active surface area exposure leads to shorter paths of charges from electrolyte to electrode surface. Moreover, a three-dimensional highly ordered mesoporous structure can facilitate diffusion and penetration of electrolyte and oxygen, and can also keep catalyst nanoparticles in a well-dispersed condition with more active sites. Electrochemical measurements revealed that 20, 50, 25 wt% are the best weight contents for M (M = Pt, Pd, Au) in the Co3 O4 with highest electrochemical activity (0.410, 0.415 and 0.422 V vs. SCE) and j 0.7V reaching a maximum value. M-Co3 O4 (M = Pt, Pd, Au) materials exhibit superior activities and excellent long-duration stability in alkaline attributed to accelerating the formation of Co(IV) cations after being introduced M(M = Pt, Pd, Au) nanoparticles within mesoporous Co3 O4 . This kind of noble metal embedded within mesoporous oxide catalysts will hold a large potential as a highly promising electrocatalyst in the future. Graphical abstract: Image 1 Highlights: Mesoporous Co3 O4 shows a high activity for oxygen evolution reaction. The structure provides more active centers and shorter paths of charges. Pt, Pd, and Au nanoparticles are uniformly dispersed in the mesoporous Co3 O4 . The optimal proportion of Pt, Pd and Au with highest activity has been studied. XPS proves formation Co(IV) by introducing Pt, Pd and Au.